Dysfunction of the Heteromeric KV7.3/KV7.5 Potassium Channel is Associated with Autism Spectrum Disorders - Gilling, Mette; Rasmussen, Hanne B.; Calloe, Kirstine; Sequeira, Ana F.; Baretto, Marta; Oliveira, Guiomar; Almeida, Joana; Lauritsen, Marlene B.; Ullmann, Reinhard; Boonen, Susanne E.; Brøndum-Nielsen, Karen; Kalscheuer, Vera M.; et al. (Frontiers in Genetics, 2013)
Heterozygous mutations in the KCNQ3 gene on chromosome 8q24 encoding the voltage-gated potassium channel KV7.3 subunit have previously been associated with rolandic epilepsy and idiopathic generalized epilepsy (IGE) including benign neonatal convulsions. We identified a de novo t(3;8)(q21;q24) translocation truncating KCNQ3 in a boy with childhood autism. In addition, we identified a c.1720C>T [p.P574S] nucleotide change in three unrelated individuals with childhood autism and no history of convulsions. This nucleotide change was previously reported in patients with rolandic epilepsy or IGE and has now been annotated as a very rare SNP (rs74582884) in dbSNP. The p.P574S Kv7.3 variant significantly reduced potassium current amplitude in Xenopus laevis oocytes when co-expressed with Kv7.5 but not with Kv7.2 or Kv7.4. The nucleotide change did not affect trafficking of heteromeric mutant Kv7.3/2, Kv7.3/4 or Kv7.3/5 channels in HEK 293 cells or primary rat hippocampal neurons. Our results suggest that dysfunction of the heteromeric Kv7.3/5 channel is implicated in the pathogenesis of some forms of autism spectrum disorders (ASD), epilepsy and possibly other psychiatric disorders and therefore, KCNQ3 and KCNQ5 are suggested as candidate genes for these disorders.